Des paysages agroforestiers à l’interface entre ressource, production et conservation (Uttarakhand, Inde) - Sylvie Guillerme (Projets de Paysage)
In India, where population density exacerbates environmental, economic and social problems, agroforestry associations play a key role in the composition of rural landscapes. This is particularly the case in Uttarakhand, a mountain State in North-East India which offers a wide diversity of forestry and agroforestry landscapes in an area stretching from the fertile Ganges Plain to the snow-covered summits of the Himalayas. In such a context, and faced with an environmental and protectionist forestry policy inherited from the British colonial period, village communities are blamed for the degradation of the forests in spite of their ancestral use of these forests in association with agroforestry farming practices in the cultivated areas. This article, based on field work conducted in each of the two agroecological zones of this State (Himalayan mountains and Indo-Gangetic plain), sheds light on the challenges faced by small farmers due to the 2014 law for the promotion of the National Agroforestry Policy.